Financial Literacy as Citizenship Education – a viable prospect? - Björklund, Mattias; Sandahl, Johan (JSSE - Journal of Social Science Education, 2020)
Purpose: This article aims to discuss what kind of teaching is required to enable students to critically review financial issues in a way that is in accordance with a broad citizenship education. Method: Content analysis where an assessment of students’ answers was compared and aligned with Westheimer & Kahne’s (2004) theory driven conceptions of citizenship. Findings: Findings demonstrate that students’ understandings correspond with the three conceptions and give important indications of what needs to be included in teaching in order to address financial issues as citizenship education. Implications: Focus in financial literacy education should be widened to include political and social aspects of the relation between households and the financial systems.